2022
DOI: 10.1128/spectrum.01039-22
|View full text |Cite
|
Sign up to set email alerts
|

Cefadroxil Comparable to Cephalexin: Minimum Inhibitory Concentrations among Methicillin-Susceptible Staphylococcus aureus Isolates from Pediatric Musculoskeletal Infections

Abstract: Cephalexin and cefadroxil are oral antibiotics that are used to treat serious infections due to the bacteria MSSA. While cephalexin is used more commonly, cefadroxil is excreted from the body more slowly; this generally allows patients to take cefadroxil less frequently than cephalexin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other studies have demonstrated success in use of cefadroxil for treatment of AHO in children [ 19 ]. Previous recommendations have suggested cefadroxil dosing of 100 to 150 mg/kg/d divided 2 or 3 times per day, for treatment of osteomyelitis, though more recent literature has demonstrated success with much lower doses (30 mg/kg/d divided twice per day) [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated success in use of cefadroxil for treatment of AHO in children [ 19 ]. Previous recommendations have suggested cefadroxil dosing of 100 to 150 mg/kg/d divided 2 or 3 times per day, for treatment of osteomyelitis, though more recent literature has demonstrated success with much lower doses (30 mg/kg/d divided twice per day) [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the release studies, it can be inferred that the concentrations exceed the limit needed for the effective inhibition of clinically relevant, infection-causing pathogens. For example, the minimum inhibitory concentration (MIC) of cephalexin required to treat methicillin-sensitive Staphylococcus aureus (MSSA) infections is 2 µg mL −1 [55]. For Met, an effective MIC against many anaerobic bacterial strains ranges between 0.125 µg mL −1 and 1 µg mL −1 indicating the potential application of these composites for biomedical applications, such as in developing antimicrobial gauze and disinfectant surfaces [11,56,57].…”
Section: Drug Release Profilementioning
confidence: 99%